A Comment on "Vulnerability and Clientelism" (2022) - Hai Ma; Sébastien Montpetit; Ardyn Nordstrom (Institute for Replication (I4R), 2023)
The paper estimates the effect that changes in household vulnerability have on citizens' participation in clientelist relationships. The authors exploit two sources of variation in household vulnerability: rainfall shocks, and a randomized intervention that provided cisterns in drought-prone areas. We reproduce all the findings presented in the four main results tables presented in the paper. The results of our robustness replication show that the results in the original paper are robust to variations in the rainfall period used as a baseline to assess changes in household vulnerability, and to exclusions that eliminate individuals in the sample who may have been substituted with others at different survey points. However, some of the original results that explain the underlying mechanisms are sensitive to how "clientelist relationships" are defined. When more frequent interactions with politicians are used as the defining characteristic of households in clientelist relationships, we find that the original results suggesting clientelism as a significant mechanism are no longer statistically significant at any standard significance level. We note, however, that the authors, in a reply to questions we sent them after the Replication Games, convincingly show that their results are robust to changing the definition of the clientelist marker.
Keywords: 330